2021
DOI: 10.4103/ipj.ipj_74_21
|View full text |Cite
|
Sign up to set email alerts
|

Awareness among parents of individuals with intellectual disability about sexual health education

Abstract: Background: Most of the parents have no idea that how and when they should educate about sexual health to their typically growing children. It is important for parents to educate their children with intellectual disability about sexual health. The risk of sexual exploitation and abuse is very high in individuals with intellectual disability. Objective: The present study was conducted to find out the awareness among the parents of individuals with intellectual disability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Previous research that resonates with this study found that knowledge is good if shared with caregivers who require it to meet the children’s developmental needs [ 41 ]. However, the empowerment of families of children with ID is mainly determined by their economic status and educational level [ 42 , 43 ]. In support, previous results indicate that the caregivers’ awareness of ID is allied to resilience ability, which mainly enhances the care of children with ID [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research that resonates with this study found that knowledge is good if shared with caregivers who require it to meet the children’s developmental needs [ 41 ]. However, the empowerment of families of children with ID is mainly determined by their economic status and educational level [ 42 , 43 ]. In support, previous results indicate that the caregivers’ awareness of ID is allied to resilience ability, which mainly enhances the care of children with ID [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a primary caregiver, every family is an environment where essential interpersonal experiences of a child’s development occur [ 7 ], including personality, behaviour, and attitudes. Even though families take the lead in raising these children, ID awareness and information among the carers has been a continued concern [ 8 ]. In addition, information created for childrearing may not benefit caregivers of children with ID [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Araştırmada ebeveynler içinde gerekli görülen cinsel eğitim konuları alanyazındaki diğer araştırma bulguları ile paralel olarak; ereksiyon, mastürbasyon, ped kullanımı, mahremiyet, cinsel sosyalleşme, güvenlik, istismardan korunma ve toplumsal kabul ile sınırlı kalmıştır (Ballan 2012;Eyres vd., 2022;Lafferty vd., 2012;Rooks-Ellis vd., 2020;Saini & Nazli, 2021). Bu çalışmada ebeveynler için çocuklarına kimin cinsel eğitim vereceği önemlidir.…”
Section: Discussionunclassified
“…It is evident from the studies that despite the increasing acceptance and knowledge of society, especially among caregivers, about the dimensions of sexuality in women with ID, some aspects of sexuality are still controversial in this group. This issue may vary according to the cultural, moral and religious conditions of each society [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%